Da leitura à poesia: da poesia à leitura - Nóbrega, Francisca Vânia Rocha (2016)
This study aimed to present poetry as an efficient didactic and pedagogical tool in acquisition of proficient reading in Portuguese classes in elementary school. This choice of gender is justified by the fact that poetry offers a wide array of reading due to its polyphonic, multi significant, full of symbology, images, representations and subjectivity of many values that permeated or permeate our society. According to Bossi (1983), the poetic activity seeks an intense relationship with the "world-of-life". Thus, the poetry gender will be used in the perspective of school literacy, as a social conception of reading. In this approach, to literate is more than alphabetize, it is to teach reading and writing in a context in which this actions are meaningful and a part of the student’s daily routine. Based in this premise, this research sides with the conception that to literacy is more than a simple set of individual skills, it is a set of social practices related to reading and writing in which subjects are involved in its social context. To fulfill our goal, the theoretical foundation is based on the studies of Bakhtin (1995), Gadamer (1997), Silva (1989), Soares (2012), Kleiman (2012), Paes (1991), Lyra (1986), Cosson (2012), Jouve (2012), Nunes (1996) Pinheiro (2000), among others. To literate following the poetry bias is to develop in the students the “me-you-world” dialogue practice. It is also the way to the appropriation of the full reading, which, according to Antunes (2003), occurs when the reader arrives at the interpretation of the ideological aspects of the text, interpreting conceptions that sometimes are embedded between the text lines, grasping the meaning expressed in the fabric of the statement, be it poetic or not. The methodology used in this research envelops both literature and qualitative research, considering that subjects are teenage students belonging to the belonging to the state level of elementary school located at the neighborhood of Mangabeira (João Pessoa – Brazil).